2021
DOI: 10.1002/bio.4056
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics on fluorescence quenching of rhodamine 6G by graphene oxide

Abstract: Fluorescence quenching of rhodamine 6G by graphene oxide (GO) was investigated using steady‐state fluorescence spectroscopy and ultrafast time‐resolved absorption spectroscopy. The steady‐state fluorescence spectra showed that rhodamine 6G fluorescence was effectively quenched by titrating the GO to the rhodamine 6G solutions. For lower GO concentrations, transient dynamic curves followed two‐exponential decay parameters. For higher GO concentrations, the dynamic curves could not be fitted well, and three‐expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Next, we specifically analyze the application of TAS in such composite materials. Dunli Liu et al [37] used fluorescence spectroscopy and TAS to study the fluorescence quenching effect of different concentrations of GO on R6G, as shown in Figure 6(a-c). The authors investigated the Reproduced with permission.…”
Section: Gnds-organic Dye Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we specifically analyze the application of TAS in such composite materials. Dunli Liu et al [37] used fluorescence spectroscopy and TAS to study the fluorescence quenching effect of different concentrations of GO on R6G, as shown in Figure 6(a-c). The authors investigated the Reproduced with permission.…”
Section: Gnds-organic Dye Compositesmentioning
confidence: 99%
“…The authors investigated the Reproduced with permission. [37] Copyright 2021, Wiley-VCH. (d) The GSB signal decay kinetics of RdB and RdB-(R)GO at 560 nm (λex = 490 nm); (e) The ET mechanism in RdB-(R)GO.…”
Section: Gnds-organic Dye Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Driven by their potential impact on energy technology, graphene and GO have been widely characterized for the energy/charge transfer between them and other donors or acceptors. GO is commonly considered a fluorescence quencher for fluorophores [ 18 , 19 , 20 ] and fluorescent biomolecules [ 21 , 22 , 23 ], mainly due to energy transfer, electron transfer and non-radiative dipole–dipole coupling channels [ 24 ]. Albeit fluorescence enhancement effects may occur under certain conditions (as described at the end of this section), GO is typically considered a fluorescence quencher and is used as such for sensing applications.…”
Section: The Role Of Go In Fluorescence Detectionmentioning
confidence: 99%